2022
DOI: 10.1007/s00520-021-06639-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status alterations after chimeric antigen receptor T cell therapy in patients with hematological malignancies: a retrospective study

Abstract: Purpose: The in uence of innovative chimeric antigen receptor T cell (CAR-T) therapy for hematological malignancies on nutritional status remains unknown. Therefore, we aim to explore the alterations of nutritional status after CAR-T therapy in patients with hematological malignancies. Methods: We retrospectively collected the data of patients with acute leukemia (AL), lymphoma and multiple myeloma (MM), who underwent CAR-T therapy at our hospital from 2018 to 2020. The serum albumin, triglyceride and choleste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The prevalence of neurotoxicity in our CAR‐T cohort concur with the lower rates reported among CAR‐T trials in NHL, ranging from 20% to 64% 43,44 . A previous retrospective audit identified that 18% of patients with neurotoxicity ( n = 4) had on average 8.8% weight loss and all required EN 17 . The present study has implicated that neurotoxicity was associated with weight loss of 6 kg within a 30‐day period post‐treatment, indicating a need to support these patients dietetically.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The prevalence of neurotoxicity in our CAR‐T cohort concur with the lower rates reported among CAR‐T trials in NHL, ranging from 20% to 64% 43,44 . A previous retrospective audit identified that 18% of patients with neurotoxicity ( n = 4) had on average 8.8% weight loss and all required EN 17 . The present study has implicated that neurotoxicity was associated with weight loss of 6 kg within a 30‐day period post‐treatment, indicating a need to support these patients dietetically.…”
Section: Discussionsupporting
confidence: 85%
“…16 Another study measured changes in nutrition-related biochemical markers (albumin, triglycerides and cholesterol) during CAR-T therapy, which are not reliable markers of acute nutrition status or body composition changes. 17,18 However, preliminary audit data collected at King's College Hospital based on 40 adults with NHL identified 25% of patients to be malnourished pre-CAR-T therapy, whereas 67% of patients were not impacted by ≥ 5% weight loss of body weight during their hospital admission following CAR-T therapy. 19 The lower prevalence of weight loss was likely attributed by an observed lower prevalence of NIS following CAR-T therapy compared to other treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse mesothelin-expressing pancreatic carcinoma model, the inhibition of cholesterol acyltransferase 1 (ACAT-1) in CAR-T cells resulted in significant tumor regression 46 . Cholesterol levels were reduced after CAR-T cell infusion in several hematological malignancies, suggesting that cholesterol metabolism may impact CAR-T cell therapy 47 . In ovarian cancer cells, membrane cholesterol efflux drives TAM-mediated tumor progression 26 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analysis has confirmed that CRS is an independent risk factor of post-CAR-T hypoalbuminemia. Meanwhile, our previous retrospective study has also found that the albumin level and total cholesterol level after CAR-T cell infusion was negatively correlated with CRS grades [ 13 ]. Therefore, we reasonably hypothesized that a unique mechanism exists wherein CRS contributes to post-CAR-T hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 99%